A spatial map of MAPK-activated immunosuppressive myeloid populations in pediatric low-grade glioma - Andrade, Augusto Faria; Sigaud, Romain; Puligandla, Evan; Liu, Bridget; Karimi, Elham; Annett, Alva; Rezanejad, Morteza; Jawhar, Wajih; Taylor, Robert; Cao, Yi; Schmid, Simone; Selt, Florian; et al. (Nature immunology, 2025)
Pediatric low-grade gliomas (pLGGs) are mitogen-activated protein kinase (MAPK) pathway-activated brain tumors prevalent in children and are associated with morbidity despite favorable survival. Here using imaging mass cytometry, we spatially characterized at the single-cell level the tumor microenvironment (TME) of 120 pLGG cases, considering age, molecular drivers, brain location and tumor subtype. Our analysis identified myeloid cells—including resident microglia and bone marrow-derived macrophages—as the predominant immune population in the TME, particularly in optic pathway tumors. Additionally, we discovered an immune signature predictive of progression-free survival. Spatial analysis identified specific cellular interactions, notably myeloid-myeloid contacts and macrophage-enriched regions harboring MAPK-activated, TIM-3+ myeloid cells, suggesting an immunosuppressive TME. Our study provides a comprehensive resource on the immune landscape of these pLGGs and underscores the immunosuppressive role of diverse myeloid infiltrates. These findings also indicate that combining TIM-3 blockade with MAPK inhibition might be a promising therapeutic strategy to target both the TME and oncogenic MAPK activation in pLGG tumors.